2016
DOI: 10.1111/cen.13100
|View full text |Cite
|
Sign up to set email alerts
|

Serum 25‐hydroxyvitamin D and insulin resistance in people at high risk of cardiovascular disease: a euglycaemic hyperinsulinaemic clamp study

Abstract: word count: 210References: 28 Number of tables: 3 Number of figures: 2Trial Registration: NCT00874341, ClinicalTrials.gov pg. 3 ABSTRACT CONTEXT: In observational studies low serum concentration is associated with an increased risk of type 2 diabetes mellitus (DM).Increasing serum 25-OHD may have beneficial effects on insulin resistance or betacell function. Cross-sectional studies utilising sub-optimal methods for assessment of insulin sensitivity and serum 25-OHD concentration provide conflicting results. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 28 publications
1
1
0
Order By: Relevance
“…Weak associations were observed between vitamin D and HOMA-b, while the association with fasting plasma glucose approached significance. Overall, these results suggest that vitamin D does not have a role in the development of GDM during pregnancy and are consistent with evolving data in the non-pregnant context [35,36]. The positive association of 25OHD and HDL merits further investigation to confirm the association and to explore possible biological mechanisms.…”
Section: Discussionsupporting
confidence: 88%
“…Weak associations were observed between vitamin D and HOMA-b, while the association with fasting plasma glucose approached significance. Overall, these results suggest that vitamin D does not have a role in the development of GDM during pregnancy and are consistent with evolving data in the non-pregnant context [35,36]. The positive association of 25OHD and HDL merits further investigation to confirm the association and to explore possible biological mechanisms.…”
Section: Discussionsupporting
confidence: 88%
“…Conversely, several studies showed positive associations between serum vitamin D levels and peripheral insulin sensitivity in both pre-diabetic and T2D subjects [ 79 , 80 ]. Four out of six cross-sectional studies using euglycemic stepped hyperinsulinemic clamps, considered the gold standard for measuring insulin sensitivity, showed positive associations between vitamin D levels and insulin sensitivity in non-diabetic subjects [ [81] , [82] , [83] , [84] , [85] , [86] ]. Prospective studies also revealed beneficial effects of vitamin D supplementation on insulin sensitivity [ 87 , 88 ], including a meta-analysis of prospective cohort studies [ 17 , 89 , 90 ].…”
Section: Discussionmentioning
confidence: 99%